The 2D Zakharov-Kuznetsov-Burgers equation on a strip - Nikolai Andreevitch Larkin (Boletim da Sociedade Paranaense de Matemática, 2016)
An initial-boundary value problem for the 2D Zakharov-Kuznetsov-Burgers equation posed on a channel-type strip was considered. The existence and uniqueness results for regular and weak solutions in wieighted spaces as well as exponential decay of small solutions without restricitions on the width of a strip were proven both for regular solutions in an elevated norm and for weak solutions in the $L^2$-norm.